Carcinoma of Unknown Primary and the 8th Edition TNM Classification for Head and Neck Cancer. (18th March 2021) - Boeker, Robert; Stromberger, Carmen; Heiland, Max; Beck‐Broichsitter, Benedicta; Hofmann, Veit M.; Neumann, Konrad; Ochsenreither, Sebastian; Olze, Heidi; Dommerich, Steffen; Piwonski, Iris; Coordes, Annekatrin
Abstract : Objective: In the 8th Edition TNM Classification for Head and Neck Cancer, the classification for carcinoma of unknown primary (CUP) changed in addition to oropharyngeal carcinomas. The current classification considers extranodal extension (ENE), determination of p16 (surrogate marker for human papillomavirus), and detection of Epstein‐Barr virus (EBV). The aim of this study was to investigate the influence of the new classification on the prognosis of p16‐positive and p16‐negative CUP and the impact of EBV proof. Methods: Clinical and pathological data from patients with CUP of the head and neck between 2009 and 2018 were evaluated. The 7th (UICC7) and 8th (UICC8) edition of the Union for International Cancer Control staging system were applied and compared. Results: There were 97 patients treated, 26.8% women and 73.2% men. The average age at initial diagnosis was 64.6 years. Of which, 58.8% had a documented history of smoking, 37.1% were positive for p16, 4.1% were positive for EBV, and 66% had ENE. Most of the patients were at stage III/IVa (78.4% according to UICC7). According to UICC8, p16+ patients were mainly at stage I (86.1%), and p16− at stage IVb (56.1%). P16 status ( P = .002), ENE ( P = .001), nodal category (TNM7, P < .001), UICC stage (TNM7, P < .001) and UICC stage (TNM8, P < .001) had a significant impact on survival in the univariate analysis. The 8th TNM classification resulted in a downstaging of p16‐positive CUP syndromes and an upstaging of p16‐negative syndromes. Conclusion: The 8th TNM classification shows the lower UICC stage in p16‐positive CUP syndromes. The prognostic significance for survival has improved from the 7th to the 8th TNM classification. Level of Evidence using the 2011 OCEBM: Level 3. Laryngoscope, 131:E2534–E2542, 2021